Concept of Manas in Mimāṃsā Darśana - Hetal Amin; Rohit Sharma (Wolters Kluwer Medknow Publications, 2016)
There are many different traditions of religion and philosophy handed over in regular succession. Although the explanation and interpretations of all Darśanas are different from one another, all Darśanas have their own separate codes of conduct and priority. Philosophy is the prime specialty as it fulfills the ultimate goal of life with depiction of liberation of the soul. The aim of Mimāṃsā is to unravel and make clear the mysterious and complex hymns of Vedas so as to facilitate proper interpretation of Vedic texts. In Indian culture, Manas has been described by various angles. Vedic, philosophical, and Ayurvedic literature has a vast and deep description of Manas. Philosophers either"Astika" or"Nastika" have described Manas Siddhanta vividly. Although there are several kinds of differences of opinions, all Darśanas accept the importance of Manas in the process of perception and even for the birth of any individual. An attempt is made to highlight the concept of Manas in Mimāṃsā Darśana in this article.